MHD natural convection flow with radiative heat transfer past an impulsively moving vertical plate with ramped temperature in the presence of hall current and thermal diffusion - Seth, Gauri Shanker; Mahato, Goutam Kumar; Sarkar, Subharthi (Zielona Góra: Uniwersytet Zielonogórski)
An investigation on an unsteady MHD natural convection flow with radiative heat transfer of a viscous, incompressible, electrically conducting and optically thick fluid past an impulsively moving vertical plate with ramped temperature in a porous medium in the presence of a Hall current and thermal diffusion is carried out. An exact solution of momentum and energy equations, under Boussinesq and Rosseland approximations, is obtained in a closed form by the Laplace transform technique for both ramped temperature and isothermal plates.
Keywords: MHD natural convection; Hall currents; ramped temperature; thermal diffusion; thermal radiation